Respuesta :

Answer: 7 minutes

You put in 2 for x, as x represents the number of stops.
(2)^4 - 3(2)^2 + (4)(2) -5 =
7

Answer:

C) 7 minutes

Step-by-step explanation:

start with formula

g(x) = x^4 - 3x^2 + 4x - 5

substitute x with number of stops (2)

g(2) = 2^4 - 3(2^2) + 4(2) - 5

simplify using p.e.m.d.a.s: start with exponents

g(2) = 16 - 3(4) + 4(2) - 5

multiply

g(2) = 16 - 12 + 8 - 5

subtract/add

16 - 12 = 4

4 + 8 = 12

12 - 5 = 7

input: 2

output: 7

ordered pair: (2,7)

ACCESS MORE